2021
DOI: 10.3389/fcomm.2021.712658
|View full text |Cite
|
Sign up to set email alerts
|

COVID ISSUE: Visual Narratives About COVID-19 Improve Message Accessibility, Self-Efficacy, and Health Precautions

Abstract: Visual narratives are promising tools for science and health communication, especially for broad audiences in times of public health crisis, such as during the COVID-19 pandemic. In this study, we used the Lifeology illustrated “flashcard” course platform to construct visual narratives about COVID-19, and then assessed their impact on behavioral intentions. We conducted a survey experiment among 1,775 health app users. Participants viewed illustrated (sequential art) courses about: 1) sleep, 2) what COVID-19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…To date, limited research has examined the effectiveness of narratives in the context of pandemics, and existing studies have shown mixed results. 23 - 25 Bekalu et al 23 found a narrative video clip to be less effective than a non-narrative video in increasing knowledge and perceived response efficacy related to the prevention of pandemic influenza. Similarly, Kuru et al 24 compared the effectiveness of pro-MMR vaccine narratives to expert pro-vaccine science messages containing statistical information and found that the informational message outperformed the narrative one.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…To date, limited research has examined the effectiveness of narratives in the context of pandemics, and existing studies have shown mixed results. 23 - 25 Bekalu et al 23 found a narrative video clip to be less effective than a non-narrative video in increasing knowledge and perceived response efficacy related to the prevention of pandemic influenza. Similarly, Kuru et al 24 compared the effectiveness of pro-MMR vaccine narratives to expert pro-vaccine science messages containing statistical information and found that the informational message outperformed the narrative one.…”
Section: Purposementioning
confidence: 99%
“…For example, a recent study found that viewing a visual narrative course on the disease and how to protect oneself was associated with improved self-efficacy and behavioral intentions toward COVID-19 disease prevention (compared to a control course about sleep). 25 …”
Section: Purposementioning
confidence: 99%
“…In terms of current clinical trials community engagement, several initiatives explore digital arts enquiries including highly relatable, visual story‐telling aimed to boost trial diversity, 34 rigorously co‐developed visual narratives and materials supporting health literacy 35 and an in‐depth exploration of the inclusion challenges, strengths, weaknesses and practical applications of digital technologies. 36 …”
Section: Discussionmentioning
confidence: 99%
“…The outcome of their study suggested that visual narratives can improve health literacy and provide individuals with the capacity to act on health information that they may know of but find difficult to process or apply to their daily lives. 21 …”
Section: Discussionmentioning
confidence: 99%